2012
DOI: 10.1161/circinterventions.112.971630
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-Coated Balloons Reduce Restenosis After Femoro-Popliteal Angioplasty

Abstract: P ercutaneous revascularization is an established treatment for femoro-popliteal artery disease.1 Yet, restenosis, reocclusion, and ensuing symptom recurrence can occur in as many as 50% of patients undergoing percutaneous transluminal angioplasty (PTA), often requiring repeat percutaneous or surgical intervention.2,3 The superficial femoral artery represents a unique challenging vessel.4 Bare-metal stents reduce restenosis versus PTA and have gained widespread adoption. 5,6 Alternative therapies, such as drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
235
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(250 citation statements)
references
References 18 publications
5
235
1
6
Order By: Relevance
“…Based on a systematic literature review of clinical measures 17 , 12 publications including registries and clinical trials were used to estimate the TLR rates associated with each endovascular procedure studied [19][20][21][22][23][24][25][26][27][28][29]. More detailed information about TLR probabilities indicated in each study is shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a systematic literature review of clinical measures 17 , 12 publications including registries and clinical trials were used to estimate the TLR rates associated with each endovascular procedure studied [19][20][21][22][23][24][25][26][27][28][29]. More detailed information about TLR probabilities indicated in each study is shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Drug-eluting stents (DESs) which, in addition to providing structural support to the vessel, exploit the anti-proliferative actions of drugs to inhibit the process of restenosis, may be substituted 12,13 . Drug-coated balloons (DCBs) are promising alternatives for the treatment of patients with PAD due to the potential reduction in re-intervention rates compared with other technologies commonly used [14][15][16] . This analysis had multiple objectives: i) to evaluate total costs per patient associated with each with the 4 endovascular therapies currently in use for PAD (DCBs, POBA, BMSs, and DESs) at 1 year using a decision analytic model; ii) to apply the results of the 1-year analysis to estimate the total economic impact on the Italian National Healthcare Service (NHS) for peripheral interventions over a 5-year period.…”
Section: Introductionmentioning
confidence: 99%
“…In one clinical study of a drug-coated balloon which allowed stratification to stent treatment, primary stenting was selected over balloon-only treatment for approximately 25% of patients [40], and in a registry of patients treated with a drug-coated balloon, 23% of patients also had a stent implanted [41]. Provisional stenting rates after acute percutaneous angioplasty (PTA) failure in the aforementioned and other recent clinical trials averaged approximately 13% [34,36,38,40,42]. In a study designed to compare efficacy of balloon-based PTA with that of a drugcoated stent, 50% of those patients who had been randomly assigned to the PTA arm received provisional stents [4].…”
Section: Expert Opinionmentioning
confidence: 99%
“…In prospective clinical trials In relatively small CLI patient cohorts, tibial vessel drug-eluting balloon (DEB) angioplasty significantly reduced restenosis rates and late lumen loss (LLL) at 3, 6, and 12 months [68,69] Although these angiographic assessments were not core lab adjudicated, there is a growing perception that the clinical results of DEB tibial angioplasty mirror the clinical experience in the superficial femoral artery. [70,71,72,73] Ankle-brachial index (ABI) test is recommended screening test for early diagnosis of PAD in patients with signs and symptoms of lower extremity ischemia. An ABI <0.9 with values from 0.91 to 1.0, consider as borderline abnormal.…”
Section: Current Trends and Outcomes: Endovascular Management In Artementioning
confidence: 99%
“…[101] The Paclitaxel-Coated Balloons in Femoral Indication to Defeat Restenosis (PACIFIER) trial also demonstrated improved end points for DCB versus conventional angioplasty at 12 months. [102] More recently, the Lutonix Paclitaxel-Coated Balloon for the Prevention of Femoropopliteal Restenosis (LEVANT I) trial demonstrated significantly decreased mean late lumen loss for de novo SFA disease treated with the lower paclitaxel dose Lutonix DCB versus conventional balloons in patients treated with either angioplasty only or after stenting. [103] The Drug-Eluting Balloon in Peripheral Intervention for The Superficial Femoral Artery trial randomizing patients to upfront DCB or conventional angioplasty followed by stenting demonstrate similarly encouraging results at 12 months.…”
Section: Current Trends and Outcomes: Endovascular Management In Artementioning
confidence: 99%